Reimagining hanfu: An intergenerational psychological analysis of user needs and design preferences via the Kano-AHP framework - Chen Wei; Kaewboucha, Manus; Apiwathnasorn, Chalisa (Environment and Social Psychology, 2025)
The revitalization of Hanfu, the traditional Chinese dress, has recently experienced a marked cultural revival that cannot be reduced to the sphere of fashion but rather points to the complex psychological preconditions of identity construction, heritage maintenance, and consumer choice among the representatives of different generational groups. The current study employs a composite Kano Model-Analytic Hierarchy Process (Kano-AHP) framework to explore intergenerational differences in psychological needs and decision-making priorities upon which Hanfu consumption is based. Through rigorous quantitative analysis of survey data from 552 Chinese consumers across four generational cohorts (Gen Z, Millennials, Gen X, Baby Boomers), the research categorizes nine core Hanfu attributes into Must-Be, One-Dimensional, and Attractive needs using the Kano Model, while quantifying their relative importance in purchase decisions through AHP weighting. Results reveal significant intergenerational divergence (χ² = 127.43, p < 0.001) in attribute perception and prioritization. Younger consumers (Gen Z, Millennials) prioritize identity expression and aesthetic innovation, classifying Modern Design Integration (weight: 0.248) and Community Acceptance (weight: 0.201) as primary "Attractive" delighters. Conversely, older cohorts (Gen X, Boomers) emphasize cultural authenticity and functional comfort, with Historical Accuracy (weight: 0.324) and Fabric Quality (weight: 0.284) categorized as essential "Must-Be" requirements. A unified framework provides practical advice to the designers, marketers and cultural institutions so as to develop generation-specific strategies that would synchronise product development with the generation-specific psychological profiles and decision-making calculi, thus developing sustainable cultural engagement and market growth.